2019
DOI: 10.1111/ejn.14321
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation of human corticospinal axons at the level of the lumbar spinal segments

Abstract: Electrical stimulation over the mastoids or thoracic spinous processes has been used to assess subcortical contribution to corticospinal excitability, but responses are difficult to evoke in the resting lower limbs or are limited to only a few muscle groups. This might be mitigated by delivering the stimuli lower on the spinal column, where the descending tracts contain a greater relative density of motoneurons projecting to lower limb muscles. We investigated activation of the corticospinal axons innervating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 77 publications
(137 reference statements)
3
38
0
Order By: Relevance
“…The variability of responses (CV%) was comparable to published data in lower leg musculature at rest (e.g. Lewis et al., ; Škarabot et al., ), for both older (SOL: 26 ± 10, 27 ± 10 and 32 ± 16%; TA: 36 ± 18, 42 ± 21 and 31 ± 19% during static position, passive shortening and lengthening, respectively) and younger (SOL: 32 ± 12, 37 ± 14 and 30 ± 10%; TA: 39 ± 15, 35 ± 17 and 41 ± 15% during static position, passive shortening and lengthening, respectively) individuals.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…The variability of responses (CV%) was comparable to published data in lower leg musculature at rest (e.g. Lewis et al., ; Škarabot et al., ), for both older (SOL: 26 ± 10, 27 ± 10 and 32 ± 16%; TA: 36 ± 18, 42 ± 21 and 31 ± 19% during static position, passive shortening and lengthening, respectively) and younger (SOL: 32 ± 12, 37 ± 14 and 30 ± 10%; TA: 39 ± 15, 35 ± 17 and 41 ± 15% during static position, passive shortening and lengthening, respectively) individuals.…”
Section: Methodssupporting
confidence: 87%
“…The firing of muscle spindle afferents increases proportionally to the magnitude of the muscle stretch, but remains low during muscle shortening (Matthews, 2011). This behaviour influences corticospinal responses; in both upper and lower limb musculature, it has been shown that passive shortening and lengthening are accompanied by increased and decreased corticospinal excitability, respectively (Lewis & Byblow, 2002;Lewis, Byblow, & Carson, 2001;Škarabot et al, c 2019 The Authors. Experimental Physiology c 2019 The Physiological Society 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…1995), corresponding to the level of the eighth thoracic spinous process (T8) as this stimulating site has recently been shown to activate corticospinal axons at the level of lumbar spinal segments (Škarabot et al . 2019 a ). The pre‐exercise LEP was standardised to 15–25% of M max .…”
Section: Methodsmentioning
confidence: 98%
“…The anode (2.5 cm 2 ) was placed 5 cm above the upper edge of the cathode (Ugawa et al 1995), corresponding to the level of the eighth thoracic spinous process ( T 8 ). This stimulating site has recently been shown to activate corticospinal axons at the level of lumbar spinal segments (Škarabot et al 2018).…”
Section: Methodsmentioning
confidence: 99%